(untitled) (Ekonomski signali: poslovni magazin, 2012)
Nowdays, business conditions in banks are more complex and they require multi crieria approach to solving problems which allows comparation of a number of alternatives evaulated according to the predetermined criteria. The aim of this paper is to explain the importance of multi criteria decision making and, also to show possibilities of its use in resolving problems and making decisions in commercial banks. Information used in this study are based on data presented in academic journals and on usage of the softwares specialized for decision making support. This paper is intended for researchers and practitioners who deal with the principles of decision making and practitioners who make decisions in commercial banks.